The Impact of Teacher Professional Development on The Implementation of Technology-Enhanced Language Learning : Teachers’ Perspectives (A Study Conducted at SMPN 2 Monano) - Biahimo, Ivana Febrianty; Machmud, Karmila; Mestari, Sri Agriyanti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study explores the impact of Teacher Professional Development (TPD) on the implementation of Technology-Enhanced Language Learning (TELL) in English language teaching at SMPN 2 Monano. Despite the availability of training, many teachers face challenges in integrating technology due to infrastructural barriers, insufficient hands-on practice, and lack of continuous support. Using a qualitative design, the research employed interviews, classroom observations, and document analysis to investigate how TPD affects teachers’ confidence, competence, and pedagogical practices. The findings reveal that professional development encourages a shift from traditional methods to more interactive strategies aligned with the TPACK framework, leading to greater student engagement, comprehension, and confidence. However, limitations such as unequal access to devices, unstable internet connectivity, and misuse of technology persist, particularly in rural contexts. The study concludes that continuous, contextualized, and practice-based professional development is crucial to bridge the gap between training and real classroom practices, thereby promoting sustainable integration of digital tools in English language education.